From the Cradle to the Grave: the Effect of Family Background on the Career Path of Italian Men - Michele Raitano; Francesco Vona (Fondazione Eni Enrico Mattei (FEEM), 2015)
This paper investigates the influence of parental education on the returns to experience of Italian men using a new longitudinal dataset that contains detailed information on individual working histories. Our favourite panel estimates indicate that an additional year of parental education increases sons' weekly wages by 11.7% after twenty years of experience and that 71% of this effect emerges during the career. We show that this effect holds irrespective of individual abilities, and it appears the result of both a glass ceiling effect, due to the complementarity between parental education and son's abilities, and a parachute effect, associated with family labour market connections.
Keywords: J62; J24; J31; 330; Intergenerational Inequality; Parental Education; Experience-Earnings profiles; Human Capital